The 474-Kilobase-Pair Complete Genome Sequence of CeV-01B, a Virus Infecting Haptolina (Chrysochromulina) ericina (Prymnesiophyceae) - Gallot-Lavallée, Lucie (Genome Announc, 2015)
We report the complete genome sequence of CeV-01B, a large double-stranded DNA virus infecting the unicellular marine phytoplankton Haptolina (formerly Chrysochromulina) ericina. CeV-01B and its closest relative Phaeocystis globosa virus define an emerging subclade of the Megaviridae family with smaller genomes and particles than the originally described giant Mimiviridae infecting Acanthamoeba.